The material culture of death in medieval Japan - Gerhart, Karen M., 1949- (University of Hawai'i Press, 2009)
This study is the first in the English language to explore the ways medieval Japanese sought to overcome their sense of powerlessness over death. By attending to both religious practice and ritual objects used in funerals in the fourteenth and fifteenth centuries, it seeks to provide a new understanding of the relationship between the two. Karen Gerhart looks at how these special objects and rituals functioned by analyzing case studies culled from written records, diaries, and illustrated handscrolls, and by examining surviving funerary structures and painted and sculpted images.--from publisher description.